Lithium vanadium oxide (Li1.1V3O8) thick porous electrodes with high rate capacity: utilization and evolution upon extended cycling elucidated via operando energy dispersive X-ray diffraction and continuum simulation. Issue 1 (7th October 2020) - McCarthy, Alison H.; Mayilvahanan, Karthik; Dunkin, Mikaela R.; King, Steven T.; Quilty, Calvin D.; Housel, Lisa M.; Kuang, Jason; Takeuchi, Kenneth J.; Takeuchi, Esther S.; West, Alan C.; Wang, Lei; Marschilok, Amy C.
Abstract : Thick electrode design and charge transport across electrode were probed via operando EDXRD and an expanded continuum model. Abstract : The phase distribution of lithiated LVO in thick (∼500 μm) porous electrodes (TPEs) designed to facilitate both ion and electron transport was determined using synchrotron-based operando energy dispersive X-ray diffraction (EDXRD). Probing 3 positions in the TPE while cycling at a 1C rate revealed a homogeneous phase transition across the thickness of the electrode at the 1 st and 95 th cycles. Continuum modelling indicated uniform lithiation across the TPE in agreement with the EDXRD results and ascribed decreasing accessible active material to be the cause of loss in delivered capacity between the 1 st and 95 th cycles. The model was supported by the observation of significant particle fracture by SEM consistent with loss of electrical contact. Overall, the combination of operando EDXRD, continuum modeling, and ex situ measurements enabled a deeper understanding of lithium vanadium oxide transport properties under high rate extended cycling within a thick highly porous electrode architecture.